The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12884-017-1279-7
|View full text |Cite
|
Sign up to set email alerts
|

What influences birth place preferences, choices and decision-making amongst healthy women with straightforward pregnancies in the UK? A qualitative evidence synthesis using a ‘best fit’ framework approach

Abstract: BackgroundEnglish maternity care policy has supported offering women choice of birth setting for over twenty years, but only 13% of women in England currently give birth in settings other than obstetric units (OUs). It is unclear why uptake of non-OU settings for birth remains relatively low. This paper presents a synthesis of qualitative evidence which explores influences on women’s experiences of birth place choice, preference and decision-making from the perspectives of women using maternity services.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 48 publications
3
80
0
2
Order By: Relevance
“…In using the 'best fit' framework synthesis approach [41], an adapted CFIR framework will be developed which goes beyond listing determinants to illustrate the relationships between factors. This approach, adopted by other recently published reviews [42][43][44][45], may help advance the a priori framework towards being more testable. For example, the adapted CFIR framework can be used to generate a hypothesis, specifically in the context of menu labelling, to be tested in empirical research.…”
Section: Introductionmentioning
confidence: 99%
“…In using the 'best fit' framework synthesis approach [41], an adapted CFIR framework will be developed which goes beyond listing determinants to illustrate the relationships between factors. This approach, adopted by other recently published reviews [42][43][44][45], may help advance the a priori framework towards being more testable. For example, the adapted CFIR framework can be used to generate a hypothesis, specifically in the context of menu labelling, to be tested in empirical research.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that women who prefer a home birth expect to have greater personal autonomy, involvement in decision making with some control during the birth process, and avoidance of unnecessary intervention, whereas women who opt for a hospital birth are more often concerned about safety issues. [2][3][4][5][6][7][8][9][10][11][12][13][14] Previous studies from Netherlands and New Zealand 1,2 found that women who chose midwifery assisted units were mainly influenced by ease of access and the atmosphere of the unit; by contrast, women who chose a hospital birth were mostly influenced by the sense of safety, availability and confidence in medical staff, pain relief, and hospital facilities. Women also differed in their sociodemographic characteristics:…”
Section: Discussionmentioning
confidence: 99%
“…In view of the lack of information about these factors, there is a need to better understand women's birthplace preferences 10. Most studies of this topic focus mainly on factors that influence the choice between home, midwifery assisted, or hospital birth 11. The 2017 update of the National Institute for Health and Care Excellence guidance for intrapartum care 12 recommends that healthy women with low-risk pregnancies may choose the birth setting of their choice.…”
mentioning
confidence: 99%
“…Thus, a picture emerged across many sites of a haphazard, muddled pathway for gaining access to MUs, which defaulted to the dominant OU model frequently. A number of authors have critiqued the framing of birthplace choice, with evidence strongly suggesting that health-care professionals may guide women's choices by offering little information about alternatives to OU birth, 121 resulting in what has been variously called 'protecting steering' 122 or 'informed compliance'. 123,124 This was also found in our media analysis.…”
Section: Evidence Of the Undervaluing Of Midwifery-led Unitsmentioning
confidence: 99%